Exploring the optical reporting characteristics of drugs: UV-Vis spectra and conformations of the tyrosine kinase inhibitor SKF86002. (6th November 2017) - Van Dongen, Madeline; Khattab, Muhammad; Clayton, Andrew H. A.; Wang, Feng
Abstract : The ultimate understanding of drug–protein interactions relies on understanding drug behaviours in solution, at the molecular level. Abstract : The ultimate understanding of drug–protein interactions relies on understanding drug behaviours in solution, at the molecular level. The conformation of a drug contributes to drug–protein docking, hence, drug potency and spectroscopy. Some drugs, such as the anti-cancer drug SKF86002, are chromophores, which are promising tools for optical reporting, as they may change colour or fluorescence when interacting with cells. In the present study, four conformers of the tyrosine kinase inhibitor SKF86002 (stability:B >A >C >D ) were obtained withB andA from this study through optimisation, andC andD from the literature. As the global energy minimum structure, SKF86002B is 0.17 kcal mol −1, 10.75 kcal mol −1 and 12.52 kcal mol −1 lower in energy thanA, C andD, respectively. Although the total energy difference is small betweenB andA, the orientation of the fluorophenyl and the pyridinyl rings with respect to the heterocyclic imidazothiazole ring i.e., the shape, is quite different. The UV-Vis spectra of the conformers in dichloromethane solution were calculated using time dependent density functional theory. The absorption spectra ofA, B andC exhibit two major bands at 325.3 nm and 240.4 nm, in the vicinity of the measured bands, whereasD displays one major band (249.1 nm). In addition, the calculations assign the major bands to different transitions of the conformers, indicating that the UV-Vis spectrum of SKF86002 is, in fact, conformation dependent. The UV-Vis spectra of SFK86002 may serve as a useful optical reporting property for drug conformational changes in cells.